Intergenerational Earnings Persistence in Italy between Actual Father–Son Pairs Accounting for Lifecycle and Attenuation Bias. (5th June 2020) - Bloise, Francesco; Raitano, Michele
Abstract: Using a longitudinal dataset built merging administrative and survey data, we contribute to the literature on intergenerational inequality providing the first estimate of the intergenerational earnings elasticity (IGE) in Italy based on actual father–son pairs, taking into account issues related to measurement biases and comparing the size of the lifecycle bias when sons are selected by age or by potential experience (i.e. the number of years since the end of their studies). Our findings confirm that Italy is a low‐mobility country. In our baseline estimate, when sons are observed 6 years after the end of their studies, the IGE is approximately 0.41 and is robust to various measures of fathers' lifetime earnings. However, our results might be downward biased by the young age of sons. To measure the lifecycle bias and correct IGE estimates, we run the 'forward regression' of yearly earnings on lifetime earnings on a sample of workers followed for 30 years. We find that selecting sons by potential experience rather than by age reduces the lifecycle bias at young ages and the 'corrected' IGE is 0.48. The picture of Italy as a low‐mobility country is also confirmed when we measure the intergenerational association through the rank–rank slope.